Garantías Ambientales Un nuevo modelo ecológico-político para Costa Rica y el Mundo - Quesada Avendaño, Gabriel (2016)
In the last thirty years significant changes have occurred in the judicial, administrative and social systems to protect the environment. The first ecological group was born, the Comité de Defensa del Patrimonio Nacional (CDPN) and many protected areas have been created throughout the nation. One of the most important changes in the judicial system has been the introduction of an environmental amendment in the Constitution of Costa Rica (Art. 50). However, it is fundamental to introduce a Title of Environmental Guarantees in the Constitution of Costa Rica, in which the State, the public and private sector ought to defend and preserve the right to a safe environment, to maintain public domain over environmental issues, and finally, the use of the environment should be regulated by scientific and technical knowledge, so that people should have the right to environmental sustainability. Costa Rica would be the first country in the world to include Environmental Guarantees in its Constitution. This shall be an example to other nations in the world, to ensure environmental protection and finally to ensure the human race and all species their existence on Planet Earth.